On-Site–Modified Sheath to Overcome the Undesirable Catheterization of the Profunda Femoris Artery During Antegrade Femoral Access. (June 2020) - Ysa, August; Lobato, Marta; Arruabarrena, Amaia; Quintana, Ana M.; Gómez, Roberto; Ortiz de Salazar, Leire; Metcalfe, Matthew; Fonseca, Juan L.
Purpose: To present a simple method to avoid favored passage of a guidewire into the profunda femoris artery (PFA) after antegrade puncture of the common femoral artery.Technique: A 6-F conventional introducer sheath with a radiopaque distal marker is placed on the nurse's table with its side port orientated to the 12 o'clock position. A small (2–2.5 mm) oval fenestration is created on the superior aspect of the sheath about 3 cm from its tip with a size 11 surgical blade. The modified introducer is passed over the angled 0.035-inch guidewire into the PFA and gently retrieved until the tip marker is ~3 cm from the femoral bifurcation. The dilator is removed, and the guidewire is withdrawn to the level of the fenestration, manipulated through it, and advanced further into the superficial femoral artery under fluoroscopic guidance.Conclusion: When repeated passage of the guidewire down the PFA persists despite conventional manipulation of the wire or needle, an on-site modification of the sheath is an easy alternative approach for the catheterization of the superficial femoral artery.